Molecular characterization and antibiotic susceptibility of Pasteurella multocida isolated from commercial poultry farm and free-flying birds - Ateih, Sabsabi Mohammad (2019)
Pasteurella multocida has been recognized as the causative agent of various infections in a wide range of mammals and bird species. Pasteurella multocida could lead to significant losses in both poultry and wild birds. In poultry, P. multocida can cause acute septicemic disease with high morbidity and mortality; however, localized chronic infection is more often reported. Pasteurella multocida can be classified into five serogroups (A, B, D, E, and F) based on the capsular antigen. The first objective of this study is to isolate, identify, and serotype P. multocida from poultry farms in the central region of Peninsular Malaysia. A total of 372 samples, consisting of oral swabs and internal organs of chickens from 31 poultry farms, and 59 oral swabs from free-flying birds were collected in the central region of Peninsular Malaysia. P. multocida was identified using biochemical test and polymerase chain reaction (PCR). Thirty-four samples from five chicken farms were positive for P. multocida, while none of the freeflying birds contained P. multocida. All isolates were identified as serotype A, except for one isolate as serotype F using the PCR method. The second objective is to determine the antimicrobial susceptibility profile using disc diffusion method among P. multocida isolates. Test against commonly used antibiotics in poultry showed that these isolates showed high rate of resistance against erythromycin (100%), moderate rate of resistance against streptomycin (80%), enrofloxacin (80%), and susceptible to penicillin G (100%), amoxicillin (100%), gentamicin (97%), florfenicol (97%), and tetracycline (94%). The third objective is to molecularly characterize P. multocida isolates using pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). Pulsed-field gel electrophoresis results showed that 31 isolates were typable, with four distinct profiles evident among the isolates. Multi Locus Sequence Typing typing was conducted on one isolate per farm and the untypeable PFGE isolates. Seven different sequence types (ST) were identified, namely ST8, ST200, ST157, ST214, ST354, ST356, and ST357. Of these, ST354, ST356, and ST357 were identified for the first time. The fourth objective is to characterize P. multocida isolated from chicken farms in the central region of Peninsular Malaysia in between year 2000 to 2018. Thirteen isolates of P. multocida from samples submitted to the bacteriology laboratory, Faculty of Veterinary Medicine, University Putra Malaysia, Malaysia, were characterized in this objective. These isolates showed several multidrug-resistant properties against antibiotics. Three different sequence types (ST) were identified among the laboratory isolates. The finding of the study provided additional epidemiological information on the strains of P. multocida that cause outbreaks of fowl cholera in the central region of Peninsular Malaysia. The results of this study contribute to the understanding of fowl cholera status in Malaysia with relations to the genetic diversity and antimicrobial resistance.